2022
DOI: 10.26434/chemrxiv-2022-zjkjw
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Disclosing Environmental Ligands of hL-FABP and PPARγ: Should We Re-evaluate the Chemical Safety of Hydrocarbon Surfactants?

Abstract: Environmental obesogens can cause adverse health effects through activation of peroxisome proliferator-activated nuclear receptor γ (PPARγ). However, only a small portion of PPARγ ligands in the environment have been discovered to date, due to the co-occurrence of thousands of compounds. In this study, protein Affinity Purification with Nontargeted Analysis (APNA) was employed to identify ligands of human liver fatty acid binding protein (hL-FABP) and PPARγ in indoor dust and sewage sludge. A total of 84 featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…For instance, hydrocarbon surfactants were recently identified as the predominant synthetic PPARγ ligands in sewage sludge and house dust, among >40,000 mass spectrometry features . This class of compounds, together with fatty acids, explained 66.0 ± 27.1% of PPARγ activity in sewage sludge (Figure g) . In another very recent study, triclosan was exclusively identified as the sole inhibitor of FabI as well as the predominant antibacterial compound in sewage sludge, despite the co-occurrence of numerous other antibiotics and nonantibiotics (Figure h) .…”
Section: Protein Affinity Purification With Nontargeted Analysis (Apn...mentioning
confidence: 94%
See 4 more Smart Citations
“…For instance, hydrocarbon surfactants were recently identified as the predominant synthetic PPARγ ligands in sewage sludge and house dust, among >40,000 mass spectrometry features . This class of compounds, together with fatty acids, explained 66.0 ± 27.1% of PPARγ activity in sewage sludge (Figure g) . In another very recent study, triclosan was exclusively identified as the sole inhibitor of FabI as well as the predominant antibacterial compound in sewage sludge, despite the co-occurrence of numerous other antibiotics and nonantibiotics (Figure h) .…”
Section: Protein Affinity Purification With Nontargeted Analysis (Apn...mentioning
confidence: 94%
“…As mentioned above, we have already successfully applied the APNA method to multiple proteins including NRs, bacterial proteins, and transporter proteins. Unexpectedly, we have found that a very small number of chemicals often contributed to the majority of bioactivity. For instance, hydrocarbon surfactants were recently identified as the predominant synthetic PPARγ ligands in sewage sludge and house dust, among >40,000 mass spectrometry features . This class of compounds, together with fatty acids, explained 66.0 ± 27.1% of PPARγ activity in sewage sludge (Figure g) .…”
Section: Protein Affinity Purification With Nontargeted Analysis (Apn...mentioning
confidence: 97%
See 3 more Smart Citations